The Microbiome and Acne: Perspectives for Treatment - Clio Dessinioti; Andreas Katsambas (Dermatology and Therapy, 2024)
Abstract The skin microbiome consists of the microorganisms populating the human skin. Cutibacterium acnes (C. acnes, formerly named Propionibacterium acnes) is recognized as a key factor in acne development, regulating inflammatory and immune pathways. Dysbiosis has been described as the imbalance in skin microbiome homeostasis and may play a role in acne pathogenesis. Microbial interference has been shown to be a contributor to healthy skin homeostasis and staphylococcal strains may exclude acne-associated C. acnes phylotypes. In this review we present an update on the skin microbiome in acne and discuss how current acne treatments such as benzoyl peroxide, orally administered isotretinoin, and antibiotics may affect the skin microbiome homeostasis. We highlight the collateral damage of acne antibiotics on the skin microbiome, including the risk of antimicrobial resistance and the dysregulation of the microbiome equilibrium that may occur even with short-term antibiotic courses. Consequently, the interest is shifting towards new non-antibiotic pharmacological acne treatments. Orally administered spironolactone is an emerging off-label treatment for adult female patients and topical peroxisome proliferator-activated receptor gamma (PPARγ) modulation is being studied for patients with acne. The potential application of topical or oral probiotics, bacteriotherapy, and phage therapy for acne are further promising areas of future research.